Tilletia species on winter wheat grain - O. Shevchuk; T. Kyslykh; L. Holosna; O. Afanasieva (Карантин і захист рослин)
Goal. To determine the species composition of the complex of pathogens of bunt diseases of the genus Tilletia on winter wheat grain.